Combined Endovascular and Surgical Treatment of Primary Aortoesophageal Fistula - Marone, Enrico Maria (Texas Heart Institute, 2010)
Primary aortoesophageal fistula is a rare cause of massive upper gastrointestinal bleeding. Conservative treatment of aortoesophageal fistula results in a 60% in-hospital mortality rate with no late survival, and conventional surgical treatment has a reported in-hospital mortality rate that approaches 40%. Thoracic endovascular aortic repair is an innovative and less invasive technique for the treatment of aortoesophageal fistula. It enables the rapid control of aortic bleeding and prevents fatal early exsanguination. However, the technique does not repair the esophagus, and there remains a substantial risk of mediastinitis and infection of the stent-graft. Herein, we report the cases of 2 patients in whom we used a combined treatment: thoracic endovascular aortic repair and delayed surgical repair of the esophagus. The esophageal repair involved direct suture of the esophageal wall and reinforcement with an intercostal muscle flap. Early follow-up evaluations suggest that our treatment of both patients was successful. We discuss the advantages and limitations of our technical choices and briefly review the pertinent medical literature.